DUKUNGAN KAMPUS, KESIAPAN KERJA, MOTIVASI BELAJAR - Suseno, Bambang (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to explore the influence of campus support and job readiness on students' learning motivation. In the context of higher education, campus support and job readiness are considered important factors that influence the level of learning motivation. This study used a correlational quantitative design with multiple linear regression analysis to find the relationship between learning motivation (Y) and the independent variables, which are campus support (X1) and job readiness (X2). The data were looked at using statistical software. An R square value of 0.655 shows that campus support and job readiness can explain 65.5% of the variation in students' motivation to learn. The remaining variation is caused by things that are not part of the model. The results of the ANOVA test show that this regression model is significant, with an F value of 43.674 and a significance level of 0.000. This suggests that the combination of campus support and job readiness significantly influences students' learning motivation. The regression coefficients indicate that work readiness has a more dominant influence compared to campus support on learning motivation, with a coefficient value of 0.517 for work readiness and 0.213 for campus support. This finding emphasizes the importance of campuses in providing adequate support and preparing students for the workforce in order to enhance their learning motivation.